Science and Math Interest and Gender Stereotypes: The Role of Educator Gender in Informal Science Learning Sites - McGuire, Luke; Monzavi, Tina; Hoffman, Adam J.; Law, Fidelia; Irvin, Matthew J.; Winterbottom, Mark; Hartstone-Rose, Adam; Rutland, Adam; Burns, Karen P.; Butler, Laurence; Drews, Marc; Fields, Grace E.; et al. (Frontiers in Psychology, 2021)
Interest in science and math plays an important role in encouraging STEM motivation and career aspirations. This interest decreases for girls between late childhood and adolescence. Relatedly, positive mentoring experiences with female teachers can protect girls against losing interest. The present study examines whether visitors to informal science learning sites (ISLS; science centers, zoos, aquariums) differ in their expressed science and math interest, as well as their science and math stereotypes following an interaction with either a male or female educator. Participants (n = 364; early childhood, n = 151, Mage = 6.73; late childhood, n = 136, Mage = 10.01; adolescence, n = 59, Mage = 13.92) were visitors to one of four ISLS in the United States and United Kingdom. Following an interaction with a male or female educator, they reported their math and science interest and responded to math and science gender stereotype measures. Female participants reported greater interest in math following an interaction with a female educator, compared to when they interacted with a male educator. In turn, female participants who interacted with a female educator were less likely to report male-biased math gender stereotypes. Self-reported science interest did not differ as a function of educator gender. Together these findings suggest that, when aiming to encourage STEM interest and challenge gender stereotypes in informal settings, we must consider the importance of the gender of educators and learners.